Evaluation of a caudal midline glossectomy on tongue volume and upper airway cross-sectional areas in brachycephalic dogs: a cadaveric study - Colberg, Valeria T.; Kudej, Raymond K.; Moyer, Nicole; Peters, Joshua A.; Karlin, William M. (Frontiers in Veterinary Science, 2025)
IntroductionRelative macroglossia may contribute to brachycephalic obstructive airway syndrome, the pathologic disorder associated with respiratory dysfunction commonly seen in brachycephalic dogs. Recent studies on brachycephalic dogs have demonstrated a relative macroglossia along with reduced air volume in the upper airway compared to non-brachycephalic dogs. Tongue reduction glossectomy may be a surgical option to address upper airway obstruction secondary to macroglossia. The objective of this study was to evaluate the effects of a caudal midline glossectomy (CMG) on tongue volume and upper airway cross-sectional areas.MethodsCadaveric brachycephalic dogs (n = 6) were positioned with the tongue retracted and jaw nearly closed. Computed tomography was performed to evaluate tongue volume and cross-sectional areas of tongue, oropharynx, palatal soft tissue and nasopharynx at two levels, the caudal aspect of the hard palate and pterygoid hamulae. A standardized CMG was performed. Positioning and CT scan were repeated.ResultsCMG resulted in a 20% decrease in tongue volume (from 87,546 ± 21,121 to 70,259 ± 17,586 mm3; p < 0.01). CMG resulted in a 20 to 25% decrease in cross-sectional area of the tongue at both hard palate (from 1662 ± 311 to 1339 ± 254 mm2; p < 0.01) and pterygoid hamulae (from 1425 ± 222 to 1041 ± 150 mm2; p < 0.01), and 2 to 3-fold increase in cross-sectional area of the oropharynx at both hard palate (from 226 ± 68 to 595 ± 138 mm2; p < 0.01) and pterygoid hamulae (from 110 ± 64 to 351 ± 37 mm2; p < 0.01).DiscussionThis study provides preliminary guidelines toward the feasibility and potential benefit of CMG in select cases of macroglossia-associated upper airway obstruction.